2007
DOI: 10.2134/jeq2006.0355
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Organic Carbon in Runoff and Tile‐Drain Water under Corn and Forage Fertilized with Hog Manure

Abstract: Dissolved organic carbon (DOC) export from soils can play a significant role in soil C cycling and in nutrient and pollutant transport. However, information about DOC losses from agricultural soils as influenced by management practices is scarce. We compared the effects of mineral fertilizer (MF) and liquid hog manure (LHM) applications on the concentration and molecular size of DOC released in runoff and tile-drain water under corn (Zea mays L.) and forage cropping systems. Runoff and tile-drain water samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 44 publications
(63 reference statements)
7
43
0
Order By: Relevance
“…The mean gross DOC concentration of furrow runoff in 2003 (11.6 mg L −1 ) was similar to the 12.7 mg L −1 reported in rainfall runoff from corn plots in Quebec, Canada (Royer et al, 2007). This Canadian study did not assess the year to year variability in runoff DOC.…”
Section: Gross Dissolved Organic Carbon Concentrations In Furrow Runoffsupporting
confidence: 64%
See 1 more Smart Citation
“…The mean gross DOC concentration of furrow runoff in 2003 (11.6 mg L −1 ) was similar to the 12.7 mg L −1 reported in rainfall runoff from corn plots in Quebec, Canada (Royer et al, 2007). This Canadian study did not assess the year to year variability in runoff DOC.…”
Section: Gross Dissolved Organic Carbon Concentrations In Furrow Runoffsupporting
confidence: 64%
“…Kindler et al (2011) used porous cup samplers to collect soil percolation water at 65-or 100-cm soil depths in different forest, grassland, and cropland ecosystems across Europe to estimate DOC losses, but did not attempt to evaluate effects of manure applications in these systems. Similarly, researchers have studied DOC losses in drainage water, tile-drain, and runoff from grassland soils and corn or hay fields, but did not consider other C-budget components (Don and Schulze, 2008;Royer et al, 2007). Other studies have examined the DOC loadings in surface water inflows and runoff for furrow-or flood-irrigated fields, but did not compare untreated soils with manured soils or measure other C inputs and outputs (Poch et al, 2006;King et al, 2009;Lentz and Westermann, 2010;Mailapalli et al, 2010;Ruark et al, 2010;Krupa et al, 2012).…”
mentioning
confidence: 99%
“…The restored wetlands were designed to receive tile drainage water with high nutrient concentrations from surrounding agricultural fields to reduce nutrient exports to surface water. In the Midwest, tile drainage tends to have lower DOC compared to run-off (Royer et al, 2007) which mirrors the observed differences in DOC between the restored and reference wetlands.…”
Section: Water and Sediment Qualitysupporting
confidence: 56%
“…Although DOC comprises of small fractions of soil organic carbon, it acts as a buffering agent in replenishment mechanism like desorption from soil colloids, dissolution from litter, and exudation from plant roots (Six et al, 2000). Dissolved organic carbon is an important component of C cycling and it is supposed to be most active and mobile form of organic matter in soil and considered as indicator of soil health (Kalbitz et al, 2000;Royer et al, 2007;Pan et al, 2010). Although DOC represents only small parts of C pools, it appears to be involved in many processes, such as translocation of nutrient and their biogeochemistry of N and P (Kalbitz et al, 2000) microbial decomposer activities (Peichl et al, 2007).…”
Section: Organic Carbon Fractionsmentioning
confidence: 99%